A Legal Study of the Implementation of the Collective Music Royalty Management System in Indonesia - Sri Retno Widyorini; Husnia Hilmi Wahyuni; Bambang Joyo Supeno (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2025)
The collective management system regulated by Law Number 28 of 2014 concerning Copyright, Government Regulation Number 56 of 2021, and various ministerial regulations is designed to protect the economic rights of creators, related rights owners, and users of musical works through a royalty collection and distribution mechanism. However, its implementation has given rise to various normative issues, ranging from overlapping authority between LMK and LMKN, unclear licensing mechanisms, and minimal transparency in royalty distribution. This culminated in a number of creators filing judicial review lawsuits against PP 56/2021 and Permenkumham 27/2025, objecting to the system's inconsistency with copyright protection principles. This study aims to legally examine the implementation of the collective music royalty management system in Indonesia and assess its compliance with the principles of justice, legal certainty, and transparency. This study uses a normative legal approach supported by philosophical and conceptual analysis. The results of this study found that the implementation of the collective royalty management system still faces various ineffectiveness, including potential conflicts of interest, administrative burdens, and a lack of institutional accountability. This situation indicates the need for regulatory reformulation and strengthening of institutional governance so that the royalty management system can operate fairly, transparently, and sustainably to support the national music industry ecosystem.